Evaluasi Kepuasan Pelayanan Kesehatan Berdasarkan Indeks Kepuasan Masyarakat (IKM) di Puskesmas Sanggeng - Hans Sammy Marthin Salakory; Febby Sonya Matulessy; Sahrir Sillehu (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2024)
Public services are activities that benefit the community organised by the government, these activities are communal and have an impact on the satisfaction of service recipients. Puskesmas as one of the public service units is not always able to provide maximum satisfaction for the community, which in turn will have an impact on community dissatisfaction. In its activities, the Sanggeng Community Health Centre as a public service provider institution has not been able to provide excellent service to the community, causing many complaints from the community, especially regarding the attitude of officers who are less friendly, long in serving patients, and the cleanliness of the puskesamas that are less clean. This research was conducted with the aim of finding out the level of community satisfaction with services at the Sanggeng health centre. To answer the research problem, a quantitative descriptive method was used with the Community Satisfaction Index (CSI) analysis tool. The survey results show that the Sanggeng Health Centre received an CSI score of 77 with a quality score of B and good service performance. The service indicator with the highest CSI value is Facilities and infrastructure of 89 with a very good quality number (A), the indicator with the lowest CSI value is Service Time of 68 with a quality number C and service performance is not good. The other two indicators with Poor CSI are the first System, Mechanism, and Procedure, the CSI Value is 75. Second, Executor Behaviour, the CSI score is 76.